A Descriptive Study of Parenting Sense of Competence (PSOC) in unmarried early adulthood - Pradiptya S. Putri; Cahyaning Widhyastuti; Adinda Destia P. S; Luccyana Stiffany (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
Age maturity begins when individuals prepare for the wedding and become parents. Unfortunately​ , the existing fatherless phenomenon influences the individual, especially in the belief that they are to parenting. So many choose​ for no own child or tend to consider becoming a parent as things that make it difficult. Research This aims to know the parenting sense of competence (PSOC) picture in early adulthood that has not been married. Research about PSOC has been done, especially in individuals already married, but research on individuals​ unmarried in early adulthood is still tiny. Research is done using a descriptive analysis method. Data was collected through a PSOC questionnaire with 17 statement items. The respondents are individuals unmarried in early adulthood, aged 21-24 years old, who have not married. Research results show an average value of 62.0. with the average value known, as many as 92 out of 162 respondents have a PSOC that is classified as low. It means most respondents still do not believe they can care for later. For that matter, this needs to be improved so as not to impact a parent's early adulthood life moments negatively.